Turning the table: Luke's inclusive invitation to Communion. (August 2019) - Canoy, Robert W.
Luke's Gospel features an inclusive invitation to Communion at which the gospel of release is extended to saints and sinners alike. This Lukan message of inclusivity is demonstrated through examination of three texts: 4:16–30; 7:36–50; and 14:1–24. Following Luke's Eucharistic perspective, contemporary practices of the Lord's Supper will reorient the Supper to Jesus as Lord of the table, and in so doing overcome divisions, remove barriers, and abandon otherwise destructive cultural norms and practices often associated with the Eucharist.